Edukasi Pencegahan Stunting Melalui Posyandu dan Remaja Anti Pernikahan Dini Desa Garahan - Riko Julian Vernanda; Riza Yuli Rusdiana; Laily Majidatul Munawaroh; Inayatul Maula; Verlinda Octavia Pribowo; Siti Maghfiroh; Abdul Halim Faiz Aqil; Elok Zulaikha (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Basically, early marriage and stunting are two related aspects. Early marriage may result in many problems, such as poverty and lack of education. The lack of nutritional fulfillment and parenting education can inhibit child growth and development. The socialization held by KKN-K group 53 aims to prevent stunting by providing education about early marriage and the risk of stunting to the community in Garahan Village by having socialization in Posyandu (Integrated Service Post), secondary school, and high school. The method used in this paper is counseling by providing a forum to discuss factors, risks, and problems of early marriage and stunting. In its implementation, the socialization about early marriage and stunting gets a good appreciation and positive reaction from the community. The community got additional education about stunting as an aspect that people often are unaware of. KKN-K Group 053 appeals to the people in Garahan Village to avoid early marriage and focus on improving personal qualities as well as a bright future. In addition, the community needs to provide good parenting, especially the fulfillment of nutrition for children.